1999
DOI: 10.1073/pnas.96.20.11317
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the CDH1-associated form of the anaphase-promoting complex in postmitotic neurons

Abstract: The anaphase-promoting complex͞cyclo-some (APC) is a tightly cell cycle-regulated ubiquitin-protein ligase that targets cyclin B and other destruction boxcontaining proteins for proteolysis at the end of mitosis and in G1. Recent work has shown that activation of the APC in mitosis depends on CDC20, whereas APC is maintained active in G1 via association with the CDC20-related protein CDH1. Here we show that the mitotic activator CDC20 is the only component of the APC ubiquitination pathway whose expression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
160
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(164 citation statements)
references
References 29 publications
3
160
0
1
Order By: Relevance
“…In addition to its key regulatory function during cell proliferation, the APC/C is known to be also active in postmitotic differentiated cells (Gieffers et al 1999). However, the significance of this activity is not understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its key regulatory function during cell proliferation, the APC/C is known to be also active in postmitotic differentiated cells (Gieffers et al 1999). However, the significance of this activity is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Most if not all APC/C subunits as well as Cdh1-like proteins are found in tissues composed of fully differentiated cells (Gieffers et al 1999). Indeed, a fully active complex can be isolated from adult mouse brain tissues.…”
mentioning
confidence: 99%
“…Indeed, our results shown in Figures 2d and e confirm this notion in our cell model, since expression of Skp2Ddb mutant, refractory to Cdh1-mediated targeting, but not wild-type Skp2, prevented RA-induced p27 stabilization and cell cycle arrest in neuroblastoma cells. Previous data have reported that the APC activator Cdh1, but not Cdc20, is accumulated in postmitotic neurons (Gieffers et al, 1999;Almeida et al, 2005). Here, we directly assessed the possible involvement of APC Cdh1 in RA-induced SH-SY5Y cell differentiation.…”
mentioning
confidence: 95%
“…20). Cdh1-APC recognizes either a destruction box or a newly discovered recognition signal, the KEN box, and it is active in late mitosis and during G 1 ͞G o (19,21,22). In S phase, cell cycle-dependent phosphorylation of Cdh1 causes it to dissociate from the APC, which is then kept inactive during S phase and G 2 until the following mitosis (23).…”
mentioning
confidence: 99%